Disentangling the Structure–Activity Relationships of Naphthalene Diimides as Anticancer G-Quadruplex-Targeting Drugs - Platella, Chiara (J Med Chem, 2021)
[Image: see text] In the context of developing efficient anticancer therapies aimed at eradicating any sort of tumors, G-quadruplexes represent excellent targets. Small molecules able to interact with G-quadruplexes can interfere with cell pathways specific of tumors and common to all cancers. Naphthalene diimides (NDIs) are among the most promising, putative anticancer G-quadruplex-targeting drugs, due to their ability to simultaneously target multiple G-quadruplexes and their strong, selective in vitro and in vivo anticancer activity. Here, all the available biophysical, biological, and structural data concerning NDIs targeting G-quadruplexes were systematically analyzed. Structure–activity correlations were obtained by analyzing biophysical data of their interactions with G-quadruplex targets and control duplex structures, in parallel to biological data concerning the antiproliferative activity of NDIs on cancer and normal cells. In addition, NDI binding modes to G-quadruplexes were discussed in consideration of the structures and properties of NDIs by in-depth analysis of the available structural models of G-quadruplex/NDI complexes.